Agreement, disagreement and the NP vs. DP debate - Frank Van Eynde (Glossa, 2020)
Of special relevance for the NP vs. DP debate are nominals in which the determiner has other values for number, gender, case and/or person than the noun, for depending on whether such nominals share these values with the noun or with the determiner they provide evidence in favor of either the NP or the DP approach. This paper discusses some nominals of this kind and shows that they share the relevant feature values with the noun. It then develops an NP analysis for these nominals which is cast in the notation of Head-driven Phrase Structure Grammar. It also shows what a DP analysis would look like. A comparison reveals that the NP analyses are less complex, more uniform and less stipulative. Examples are taken from Dutch, English, German, French, Italian, Spanish, Polish and Serbo-Croatian.